Fasting and rheumatic diseases - Mohammad Hassan Jokar (Journal of Fasting and Health, 2015)
Fasting is one of the important religious practices of Muslims, in which the individuals abstain from eating and drinking from dawn to sunset. Fasting is not obligatory or even not allowed, in case it causes health problems to the fasting individual. Rheumatic diseases are a major group of chronic diseases which can bring about numerous problems while fasting. The aim of this article is to review the impact of Islamic fasting on rheumatic patients, based on the scientific evidences.